If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(4x+1)=-3(2x-3)+2x
We move all terms to the left:
2(4x+1)-(-3(2x-3)+2x)=0
We multiply parentheses
8x-(-3(2x-3)+2x)+2=0
We calculate terms in parentheses: -(-3(2x-3)+2x), so:We get rid of parentheses
-3(2x-3)+2x
We add all the numbers together, and all the variables
2x-3(2x-3)
We multiply parentheses
2x-6x+9
We add all the numbers together, and all the variables
-4x+9
Back to the equation:
-(-4x+9)
8x+4x-9+2=0
We add all the numbers together, and all the variables
12x-7=0
We move all terms containing x to the left, all other terms to the right
12x=7
x=7/12
x=7/12
| H=210-5t | | 2x=3.5x-2 | | 9c^2-18c+8=8 | | -(n-4)-2(6-2n)=4n | | 5x-3(x+4)=-6(x-3) | | 32y=120 | | 2(2x+61)=10x+29 | | (2x+10)+(4x-16)+2x=180 | | 20+25k=15 | | -12=2+5x+2x=-9 | | 7x+7+5x+19-180=x | | −2a+3=a−12 | | 3.4x=2.6 | | 7x+7+5x+19=180 | | 2(500-y)+2y=500 | | 10x-69=6X+67 | | 4(x+6)+5=9 | | 7x-0x=15 | | 14x-90=4x+190 | | 3x+7-2(x+3)=4x-2 | | 1/2(x+12)=100 | | 2x-153=45-9x | | b-9=00 | | -1/3(6x-15)=17 | | 20n-28=1-n+2 | | -9x-49=31-14x | | -3(q+5/3)=2 | | 7x+1+9x+-7=90 | | 7x-16=x+6+4x | | 7x+1+9x+-7=180 | | 9x-46=6X+41 | | -12=2+5x+2x-9 |